2013
DOI: 10.3892/etm.2013.1296
|View full text |Cite
|
Sign up to set email alerts
|

Anti-interleukin-6 receptor antibody reduces neuropathic pain following spinal cord injury in mice

Abstract: The present study reports the beneficial effects of an anti-mouse interleukin-6 (IL-6) receptor antibody (MR16-1) on neuropathic pain in mice with spinal cord injury (SCI). Following laminectomy, contusion SCI models were produced using an Infinite Horizon (IH)-impactor. MR16-1 was continuously injected for 14 days using Alzet osmotic pumps. A mouse IL-6 ELISA kit was then used to analyze IL-6 levels in the spinal cord tissue between 12 and 72 h after injury. Motor and sensory functions were evaluated each wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…For example, Hoschouer et al 2009 reported no changes in mechanical sensitivity following contusion injury to the thoracic region, while Chen et al 2012 reported tactile allodynia in their model[40, 41]. Moreover, insensitivity has been reported at early time points and hypersensitivity at later time points, and hypersensitivity to thin filaments but hyposensitivity to thicker filaments[42, 43]. Taken together the presence and direction of tactile changes following spinal contusion injury in mice is variable across laboratories and likely relates to the level and nature of damage to the dorsal column pathway transmitting ascending mechanical touch information.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hoschouer et al 2009 reported no changes in mechanical sensitivity following contusion injury to the thoracic region, while Chen et al 2012 reported tactile allodynia in their model[40, 41]. Moreover, insensitivity has been reported at early time points and hypersensitivity at later time points, and hypersensitivity to thin filaments but hyposensitivity to thicker filaments[42, 43]. Taken together the presence and direction of tactile changes following spinal contusion injury in mice is variable across laboratories and likely relates to the level and nature of damage to the dorsal column pathway transmitting ascending mechanical touch information.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve injury upregulates IL-6 and reduction of IL-6 reduces neuropathic pain (65, 69, 70). It has been proposed that TNFα upregulates IL-6 expression via a NF-κB pathway (71).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is evidence from a mouse model that the inhibition of IL-6 activity with a monoclonal antibody against IL-6R reduces neuropathic pain (19). On one hand, it remains to be elucidated whether intracellular signaling downstream of the IL-6R/gp130 complex (e.g., by activation of the transcription factors Janus kinase and signal transducer and activator of transcription (20)) contribute to the development of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%